Memahami Mental Kerja Karyawan Melalui Analisa Worklife Balance Pada Turnover Intention Di Perrguruan Tinggi Swasta Di Bawah BUMN Gresik - Rosa Rilantiana; Bima Y.P. Pradana; Mirza Dwinanda Ilmawan (Jurnal Manajerial, 2022)
Background – Mental health is influenced by events in life that leave a great impact on personality and a person, while mental health is related to Work-life Balance and stress management. Employees who fail to achieve Work-life Balance will have high levels of stress both at work and outside of work, which can have negative consequences, especially Turnover intention. Aim – analyze the direct effect of Work-life Balance on the Turnover intention of higher education employees under BUMN in Gresik and the indirect effect of Work-life Balance through work stress. Design / methodology / approach – Quantitative research using path analysis, with a sample of 89 employees of private universities under BUMN in Gresik. Result and discussion – Work-life Balance has a significant value of 0.008 <0.05 and t-count -2.695 > t-table -1.987, so that Work-life Balance has a direct negative effect on employee Turnover intention. Job stress has a significant value of 0.530 > 0.05 and t-count 0.631 < t-table 1.987, so it has no direct effect on Turnover intention. Work-life Balance which has a significant value of 0.05 <0.05 and t-count -1.989> t-table 1.987, so it has a direct negative effect on employee work stress. Finally, Work-life Balance has a significant value of 0.53 > 0.05 and t-count -0.231 < t-table 1.987, so it does not have an indirect effect on Turnover intention through the work stress variable as an employee mediation variable. Conclusion - According to the findings from this study, the Turnover rate is influenced by work life balance directly or by mediating work stress. Research implication – Universities need to improve or be able to better balance the personal lives of employees with their personal lives, because it is found that the employee Turnover rate will decrease if employees have a good and balanced Work-life Balance. Limitations – Research related to mental through work life balance, work stress in influencing Turnover intention is limited to employees of private universities under BUMN in Gresik.